Utility Bill Payment Collection Center - Vijayakumar Bhosale, Deepak; Bhagawat Yadav, Anita; Mallapa Nile, Kajal; Babaso Mohite, Prajakta; Appasaheb Bagat, Vasundhara; Vijay Dhandore, Punam (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Objective of this venture is to oversee online interaction where in Customer can take care of the service bill through Cash, Check or DD. Like Electricity, Water and BSNL phone bills can be paid through this. Online service charge installment has become an effortless answer for the customers with occupied ways of life. Through online installment of service charges, shoppers can save time, bother and accordingly make their lives a lot simpler. Albeit online service charge installment has gotten one of the quickest developing patterns on the planet especially in the US, in the Sri Lanka nonetheless, the advancement of families’ embracing to online service charge installments is somewhat lethargic.